Global Conceptualism : Points of Origin, 1950s-1980s. - Walker Art Center, Minneapolis; Miami Art Museum, Miami; Bann, Stephen; Beke, László; Camnitzer, Luis; Enwezor, Okwui; Farver, Jane; Gao, Minglu; Gintz, Claude; Poshyananda, Apinan; Ramirez, Mari Carmen; Simon, Marilyn, L.; et al. (New York : Queens Museum of Art, 1999)
1.000 Yen Note Incident Discussion Group ; Abramovic, Marina ; Akasegawa Genpei ; Anselmo, Giovanni ; Antin, Eleanor ; Apple, Billy ; Arakawa, Shusaku ; Art & Language ; Baldessari, John ; Barrio, Artur ; Bartos, Peter ; Bennett, Gordon ; Beveridge, Karl ; Bikyoto ; Boetti, Alighiero ; Bony, Oscar ; Boshoff, Willem Hendrik Adriaan ; Broodthaers, Marcel ; Brouwn, Stanley ; Bruly-Bouabré, Frédéric ; Bul-dong, Park ; Buren, Daniel ; Burgin, Victor ; Burn, Ian ; Cadere, Andre ; Caldas, Waltercio ; Caro, Antonio ; Carreira, Ricardo ; Cha, Theresa Hak Kyung ; Chang, Chaotang ; Choi, Byung-soo ; Clark, Lygia ; Collective Actions Group ; Condé, Carol ; Costa, Eduardo ; Dadson, Philip ; Darboven, Hanne ; Debord, Guy ; Dias, Antonio ; Dibbets, Jan ; Dimitrijevic, Braco ; Erdély, Miklós ; Fabro, Luciano ; Filko, Léon Ferrari Stano ; Frampton, Hollis ; Gamboa Jr., Harry ; Geers, Kendell ; Geng Jianyi ; Gorgona Group ; Greco, Alberto ; Grippo, Victor ; Group, M ; Gu Wenda ; Haacke, Hans ; Hajas, Tibor ; Hikosaka, Naoyoshi ; Hori, Kosai ; Huang Yong Ping ; Huang, Huacheng ; Huang, Yung-sung ; Huebler, Douglas ; Huot, Robert ; Jacoby, Roberto ; Jankovic, Jozef ; Kabakov, Ilya ; Kantor, Tadeusz ; Kashihara, Etsutomu ; Kawara, On ; Kelly, Mary ; Kennedy, Peter ; Kim, Bong-joon ; Kim, Dong-won ; Kim, Yong-min ; Kim, Yong-tae ; Klein, Yves ; Koller, Julius ; Komar & Melamid ; Koraichi, Rachid ; Kosuth, Joseph ; Kozlov, Christine ; Laboratoire Agit-Art ; Lamelas, David ; LeWitt, Sol ; Lippard, Lucy ; Lozano, Lee ; Lupas, Ana ; Major, János ; Manuel, Antonio ; Manzoni, Piero ; Matsuzawa, Yutaka ; Meireles, Cildo ; Melis, Juraj ; Merz, Mario ; Mikhailov, Boris ; Mlynárcik, Alex ; Nakhova, Irina ; Neagu, Paul ; Neung-Kyung ; Newsreel, Labor ; Nomura, Hitoshi ; OHO (Group) ; etc.
biografie, bibliografie
Global Conceptualism : Points of Origin, 1950s-1980s, Queens Museum of Art, New York, April 28 - August 29, 1999 ; Walker Art Center, Minneapolis, December 19, 1999 - March 5, 2000 ; Miami Art Museum, Miami, September 15 - November 26, 2000
Engels
boek